Effect of maternal high dosages of folic acid supplements on neurocognitive development in children at 4-5 y of age: the prospective birth cohort Infancia y Medio Ambiente (INMA) study - Valera-Gran, Desirée; Navarrete-Muñoz, Eva M; Garcia de la Hera, Manuela; Fernández-Somoano, Ana; Tardón, Adonina; Ibarluzea, Jesús; Balluerka, Nekane; Murcia, Mario; González-Safont, Llúcia; Romaguera, Dora; Julvez, Jordi; Vioque, Jesús (The American journal of clinical nutrition, 2017)
The benefits of the use of folic acid supplements (FASs) during the periconception period to prevent neural tube defects and to ensure normal brain development in offspring are well known. There is concern, however, about the long-term effects of the maternal use of high dosages of FASs that exceed the Tolerable Upper Intake Level (UL) (≥1000 μg/d) on child neurocognitive outcomes. The objective of the study was to examine the association between the use of high dosages of FASs during pregnancy and child neuropsychological development at ages 4-5 y. The multicenter prospective mother-child cohort study, the Infancia y Medio Ambiente (INMA) Project, was conducted in 4 regions of Spain: Asturias, Sabadell, Gipuzkoa, and Valencia. Pregnant women were recruited between 2003 and 2008. Data on 1682 mother-child pairs were included in the final analyses. The pregnant women completed an interviewer-administered questionnaire that was validated to estimate typical dietary folate intake and the use of FASs at 10-13 and 28-32 wk of gestation. Neuropsychological development scores at 4-5 y of age were estimated with the use of the McCarthy Scales of Children's Abilities. Multiple linear regression and meta-analysis were used to obtain combined-effect estimates. During the periconception period, one-third of the women ( = 502) took FAS dosages ≥1000 μg/d. The use of FAS dosages ≥1000 μg/d in this period was negatively associated with several neuropsychological outcomes scores in children: global verbal (β = -2.49; 95% CI: -4.71, -0.27), verbal memory (β = -3.59; 95% CI: -6.95, -0.23), cognitive function of posterior cortex (β = -2.31; 95% CI: -4.45, -0.18), and cognitive function of left posterior cortex (β = -3.26; 95% CI: -5.51, -1.01). The use of FAS dosages exceeding the UL (≥1000 μg/d) during the periconception period was associated with lower levels of cognitive development in children aged 4-5 y. The use of FAS dosages ≥1000 μg/d during pregnancy should be monitored and prevented as much as possible, unless medically prescribed.